2018
DOI: 10.3390/ijerph15112433
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Heart-Healthy Behaviors among African American Adults: A Mixed Methods Study

Abstract: African Americans have a disproportionately higher risk of chronic conditions such as cardiovascular disease (CVD), type 2 diabetes, and hypertension than other ethnic or racial groups. Data regarding CVD-related perceptions and beliefs among African Americans are limited, particularly in the Southwest US. Assessment of current views regarding health and health behaviors is needed to tailor interventions to meet the unique needs of specific populations. We sought to examine knowledge, attitudes, and perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
(47 reference statements)
6
20
0
Order By: Relevance
“…African American seniors provided rich accounts about CV and related health problems, illuminating alarming patterns of chronic disease incidence and management approaches. Our results align with a recent study where African Americans identified select chronic conditions as major health concerns (e.g., stroke, diabetes, CVD) and risk factors therein for African American people (Der Ananian, Winham, Thompson, & Tisue, 2018). Participants in our study had nearly three chronic conditions, and most exhibited at least two CVDs.…”
Section: Discussionsupporting
confidence: 92%
“…African American seniors provided rich accounts about CV and related health problems, illuminating alarming patterns of chronic disease incidence and management approaches. Our results align with a recent study where African Americans identified select chronic conditions as major health concerns (e.g., stroke, diabetes, CVD) and risk factors therein for African American people (Der Ananian, Winham, Thompson, & Tisue, 2018). Participants in our study had nearly three chronic conditions, and most exhibited at least two CVDs.…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative and qualitative results from the study highlight discordance between health knowledge and health behaviors. These findings reinforce the need to investigate situation-specific perspectives before launching public health interventions [8,30,33].…”
Section: Discussionsupporting
confidence: 61%
“…The semi-structured focus group moderator guide incorporated literature review, previous research [30,31], and exploratory concepts. The socioecological model (SEM) framework guided structure of the variables for inquiry [32,33].…”
Section: Survey Instruments and Focus Group Moderator Guidementioning
confidence: 99%
“…The incidence rate of diabetes among African Americans (AAs) is approximately twice that among non-Hispanic whites. Risk factors for cardiovascular disease (CVD) in college students include obesity and physical inactivity, which are disproportionately higher among AAs [ 16 , 17 ], and studies have shown that AA college students do not consistently engage in physical activity [ 18 , 19 ]. In a study conducted at a historically black college and university (HBCU), average BP was higher among AA students than their non-Hispanic white counterparts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%